Inductively Coupled Plasma-Atomic Emission Spectrometry for the Analysis of Heavy Metals and Arsenic in Tinctures - M. S. Galenko; R. N. Alyautdin; I. V. Gravel (Регуляторные исследования и экспертиза лекарственных средств)
To ensure the safety of herbal medicinal products, particularly in liquid dosage forms, it is necessary to control environmental toxins to acceptable levels. However, there is no methodology for individual elemental impurities in tinctures. The aim of the study was to select sample preparation conditions for quantitative determination of heavy metals and arsenic in tinctures. Materials and methods: the study used tinctures of anomalous peony, motherwort and valerian sampled from pharmacies. Sample preparation involved microwave-assisted digestion of pre-concentrated aliquots. Quantitative determination of 16 elemental impurities (As, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sb, Sr, Ti, V, Zn, Hg) was carried out using inductively coupled plasma–atomic emission spectrometry. Results: according to the study results, quantitative analysis of most elemental impurities requires sample concentration at the preparation step. Due to the method sensitivity, direct quantification of individual elements in a sample is possible only at levels of not less than 0.1 mg/kg. The optimal volume of a tincture for concentration is 25 ml, both in terms of time efficiency and recovery of toxic elements. Conclusions: the proposed procedure showed the possibility of quantification of 16 elemental impurities in the tinctures. The concentrations of heavy metals and arsenic in the tinctures of anomalous peony, motherwort and valerian did not exceed 0.722 mg/kg. Zinc and manganese were the most abundant elemental impurities in the studied samples.